Fuqaha and Positive Law Opinions on the Permanent Nature of Waqf Object Submission - Qamariyanti, Yulia; Aufa, Muhammad Fikri (Program Studi Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2024)
Waqf is a virtue worship practiced by Muslims who give up their property for the public/community good. Movable and immovable assets can be donated. This paper examines fuqaha and Indonesian positive law on the permanence of waqf object surrender. Fuqaha with normative research methodologies and deductive and inductive data analysis have varied viewpoints on waqf's permanent conditions. Some require it, some don't. The first position is that waqf must be permanent and include a clear statement for it. This opinion is accepted by the majority of scholars from the Shafi'iyah, Hanafiyah, Hanabilah (excluding Abu Yusuf in one narration), Zaidiyah, Ja'fariyah, and Zahriyah. Second, jurists from the Hanabilah, Ja'fariyah, and Shafi'iyah schools say waqf might be temporary. Temporary waqf is long- and short-term. Waqf assets are institutionalized indefinitely and only land with property rights can be waqf, according to Government Regulation 28 of 1977 and Presidential Instruction 1 of 1991. Waqf conditions might be permanent or temporary, based on land rights, according to Law 41 of 2004 and Government Regulation 42 of 2006.